Corporate Capital Structure, Agency Costs, and Ownership Control: The Case of All-Equity Firms - Agrawal, Anup; Nagarajan, Nandu J. (Journal of Finance, 1990)
This paper provides evidence that all-equity firms exhibit greater levels of managerial stockholdings, more extensive family relationships among top management, and higher liquidity positions than a matched sample of levered firms. Further, top managers of all-equity firms with family involvement in corporate operations have greater control of corporate voting rights than managers of all-equity firms without family involvement. These findings are consistent with the interpretation that managerial control of voting rights and family relationships among senior managers are important factors in the decision to eliminate leverage.